Prevalence and Influencing Factors of Coronary Heart Disease and Stroke in Chinese Rural Adults: The Henan Rural Cohort Study - Wang, Yan; Li, Yuqian; Liu, Xiaotian; Zhang, Haiqing; Abdulai, Tanko; Tu, Runqi; Tian, Zhongyan; Qian, Xinling; Jiang, Jingjing; Qiao, Dou; Liu, Xue; Dong, Xiaokang; et al. (Frontiers in Public Health, 2020)
Background: Epidemiological studies about cardiovascular disease in rural areas of developing countries are rare. This study aimed to estimate the prevalence and influencing factors of coronary heart disease (CHD) and stroke in Chinese rural population. Methods: 39,259 subjects (15,490 males) aged 18-79 years were enrolled from the Henan Rural Cohort Study. Age-standardized prevalence was calculated according to Chinese 6th Population Census. Associations between risk factors and diseases were estimated by the odds ratios and 95% confidence intervals with generalized linear mixed model. Results: Among the participants, 1734 with CHD and 2642 with stroke were identified. Crude prevalence of CHD was 4.42%, and prevalence in male (4.01%) was significantly lower than female (4.68%). Corresponding age-standardized prevalence was 2.23% (2.05% for male and 2.37% for female). Crude prevalence of stroke was 6.73%, and in male (7.92%) was higher than female (5.95%). Age-standardized prevalence was 2.98% (3.42% for male and 2.69% for female). The results identified that old age, female, smoking, obesity, hypertension, diabetes and dyslipidemia were positively associated with CHD. Being Female and a higher level of physical activity were negatively related to stroke, while old age, high-risk drinking and chronic disease were positively related to stroke. Conclusion: CHD and stroke were not rare in Chinese rural area. Healthy lifestyles and control of chronic disease should be improved to curb the epidemic of cardiovascular disease among rural population.